Beneath a meth moon : an elegy - Woodson, Jacqueline (New York, N.Y. : Nancy Paulsen Books, 2012)
"A young girl uses crystal meth to escape the pain of losing her mother and grandmother in Hurricane Katrina, and then struggles to get over her addiction"--
Keywords: Methamphetamine -- Fiction; Drug abuse -- Fiction; Grief -- Fiction; Runaways -- Fiction; Hurricane Katrina, 2005 -- Fiction; Iowa -- Fiction; Pass Christian (Miss.) -- Fiction; Methamphetamine -- Fiction; Drug abuse -- Fiction; Grief -- Fiction; Runaways -- Fiction; Hurricane Katrina, 2005 -- Fiction; Iowa -- Fiction; Pass Christian (Miss.) -- Fiction; JUVENILE FICTION -- Social Issues -- Drugs, Alcohol, Substance Abuse; JUVENILE FICTION -- Social Issues -- Runaways; JUVENILE FICTION -- Social Issues -- Death & Dying